2018
DOI: 10.1159/000487857
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome P450 3A5 Non-Expressor Kidney Allograft as a Risk Factor for Calcineurin Inhibitor Nephrotoxicity

Abstract: Background: Tacrolimus is mainly metabolized by cytochrome P450 3A5 (CYP3A5), which is expressed in the liver. However, CYP3A5 is also expressed in the kidney tissue and may contribute to local tacrolimus clearance in the kidney allograft. We aimed to evaluate the association between the allograft CYP3A5 genotype and transplant outcomes. Methods: We conducted a retrospective cohort study at the King Chulalongkorn Memorial Hospital, Thailand, comparing 2 groups of donor and recipient CYP3A5 genotypes, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Interindividual variability in their activities may cause variability in C Graft even when C 0Blood is controlled by TDM, potentially altering the risk of acute nephrotoxicity and the rate of development of chronic nephrotoxicity. Currently, the association between CNI nephrotoxicity and donor CYP3A5 expressor status is contradictory 21–24 . Donor ABCB1 SNPs previously linked with low P‐gp expression/activity are associated with increased risk of allograft damage, 22 CNI nephrotoxicity 25,26 and allograft loss 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Interindividual variability in their activities may cause variability in C Graft even when C 0Blood is controlled by TDM, potentially altering the risk of acute nephrotoxicity and the rate of development of chronic nephrotoxicity. Currently, the association between CNI nephrotoxicity and donor CYP3A5 expressor status is contradictory 21–24 . Donor ABCB1 SNPs previously linked with low P‐gp expression/activity are associated with increased risk of allograft damage, 22 CNI nephrotoxicity 25,26 and allograft loss 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the non‐expressor recipient may have a higher risk of CNI nephrotoxicity, while the expressor recipient may be prone to acute rejection . The expressor recipient with non‐expressor allograft has the highest risk of CNI nephrotoxicity . However, the CYP3A4*22 allele is an intronic variant associated with reduced CYP3A4 mRNA levels and CYP3A4 activity in the human liver and was estimated to be responsible for 7% of the variability in mRNA expression .…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] did demonstrate a correlation between interstitial CTGF expression and IFTA, but 5 years after kidney transplantation in contrast to the 24 months in our study. Interestingly, a larger retrospective study in 50 patients suggested an increased risk (hazard ratio, 3.18; P = .026) for developing CNIT in *1 expressors in whose who received a *3/*3 kidney allograft [ 15 ]. Alternatively, the effect of the CYP3A5 PTC genotype may be of lesser importance in the in vivo situation, in which the potential effects of higher metabolite generation is attenuated by a continuous process of removal via the urine vs. the enclosed in vitro situation, where metabolites remain in situ and the effect of the pump is less important.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of tacrolimus metabolism occurs in the gut and liver, and the genotype of these organs plays an important role in individual tacrolimus disposition. The specific genotype of the kidney for CYP3A5 and ABCB1, however, has also been associated with a differential potential for developing CNIT [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%